Use of acute and chronic ecotoxicity data in environmental risk assessment of pharmaceuticals. (4th March 2016) - Vestel, Jessica; Caldwell, Daniel J.; Constantine, Lisa; D'Aco, Vincent J.; Davidson, Todd; Dolan, David G.; Millard, Steven P.; Murray‐Smith, Richard; Parke, Neil J.; Ryan, Jim J.; Straub, Jürg Oliver; Wilson, Peter
Abstract: For many older pharmaceuticals, chronic aquatic toxicity data are limited. To assess risk during development, scale‐up, and manufacturing processes, acute data and physicochemical properties need to be leveraged to reduce potential long‐term impacts to the environment. Aquatic toxicity data were pooled from daphnid, fish, and algae studies for 102 active pharmaceutical ingredients (APIs) to evaluate the relationship between predicted no‐effect concentrations (PNECs) derived from acute and chronic tests. The relationships between acute and chronic aquatic toxicity and the n ‐octanol/water distribution coefficient ( D OW ) were also characterized. Statistically significant but weak correlations were observed between toxicity and log D OW, indicating that D OW is not the only contributor to toxicity. Both acute and chronic PNEC values could be calculated for 60 of the 102 APIs. For most compounds, PNECs derived from acute data were lower than PNECs derived from chronic data, with the exception of steroid estrogens. Seven percent of the PNECs derived from acute data were below the European Union action limit of 0.01 μg/L and all were anti‐infectives affecting algal species. Eight percent of available PNECs derived from chronic data were below the European Union action limit, and fish were the most sensitive species for all but 1 API. These analyses suggest that the use of acute data may be acceptable if chronic data are unavailable, unless specific mode of action concerns suggest otherwise. Environ Toxicol Chem 2016;35:1201–1212. © 2015 The Authors. Environmental Toxicology and Chemistry Published by Wiley Periodicals, Inc. on behalf of SETAC.